PREVALENCE OF HIV-1/HTLV-1 CO-INFECTION AND BEHAVIORAL RISK AMONG PEOPLE LIVING WITH HIV IN BELO HORIZONTE, BRAZIL - Poliane Cristina Vertêlo; Alexandre Braga Miranda; Ludimila Labanca; Ana Lúcia Borges-Starling; Cláudio Daniel Cerdeira; Carlos Felipe Nogueira; Denise Utsch Gonçalves (Universidad Nacional de Córdoba, 2023)
Objective: To analyze the prevalence of HIV-1 and HTLV-1 co-infection and risk behavioral for sexually transmitted infections (STIs) and the quality of life among people living with HIV-1 (PL-HIV-1). Methods: 985 PL-HIV-1 in Belo Horizonte (Brazil) underwent serologic immunoassay screening for HTLV-1. Fifteen people confirmed (Western blot) for HIV-1/HTLV-1 co-infection (HIV-1/HTLV-1 group) were then compared to 30 HIV-1 (HIV-1 group) and 30 HTLV-1 (HTLV-1 group) patients, matched groups for biological sex and age, and was analyzed the sociodemographic status/quality of life and risk/behavioral factors for STIs.   Results: The prevalence of HIV-1/HTLV-1 co-infection was 1.5%. The average age of the three groups was 57 (± 11) years old, with 9 and 18 (60%) women within the HIV-1/HTLV-1 and HIV-1 or HTLV-1 groups, respectively. Heterosexual orientation predominated within the three groups. The HIV-1/HTLV-1 and HIV-1 groups had most no fixed partner (p = 0.013), were single (p = 0.001) and referred condom use (p = 0.025). Most the HTLV-1 group had fixed partner, were married, and did not use condom (p = 0.025). Among other STIs, syphilis was common within the HIV-1/HTLV-1 (34%) and HIV-1 (17%) groups, and gonorrhea (13%) within the HTLV-1 group. Intravenous drug use (IDU) in the HIV-1 group was associated with co-infection (p = 0.038), and the quality of life differed among the groups.   Conclusions: HIV-1 and HIV-1/HTLV-1 groups had different risk behaviors than HTLV-1 group. The measures to prevent the spread of HIV-1 and HTLV-1 should also highlight IDU in PL-HIV-1 and condom use in people living with HTLV-1.